EFEKTIVITAS PROGRAM KARTU TANI DI DESA LINGGASARI KECAMATAN KEMBARAN KABUPATEN BANYUMAS - Fanti, Luna Almira; Kurniasih, Denok; Tobirin, Tobirin (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
The implementation of the Farmer's Card program is a form of government attention to the welfare of farmers in Indonesia. The Farmer's Card is an example of a public service, especially for farmers, which is intended to be used when buying subsidized fertilizer. The implementation of the Farmer Card service is carried out directly by the Agricultural Extension Center (BPP) with Bank Rankyat Indonesia (BRI) as well as fertilizer sellers or retailers. The aim of this research is to determine the effectiveness of the farmer card program in Linggasari Village, Kembaran District, Banyumas Regency. This research uses a descriptive method with a qualitative approach. The effectiveness of the program in this research uses indicators; 1) target success, 2) goal achievement, 3) availability of work facilities and infrastructure, 4) supervision system. The results of the research show that the farmer card program in Linggasari Village, Kembaran District, Banyumas Regency has had a positive impact on farmers in Linggasari Village to get easy access to get subsidized fertilizer at prices set by the central government. Suggestions given include routine outreach, regeneration related to elderly human resources, coordination between retailers complete with kiosks, farmers, and the Banyumas Regency Agricultural Extension Center.